LULAMENT AS A VOICE OF CULTURAL SUSTAINABILITY: FROM INTIMACY TO A CULTURAL HERITAGE STRATEGY (Heritage, 2026)
This paper explores the concept of lulament as an interdisciplinary category at the intersection of art, cultural heritage management, and intangible cultural preservation. Through the analysis of vocal practices such as lullabies and laments, lulament is presented as an alternative form of cultural articulation that connects intimate, feminine, and minority voices with strategies of cultural memory and affective knowledge. The study draws on theoretical approaches in memory studies, affect theory, feminist critique, and artistic research to argue that lulament can function as a mode of social and cultural cohesion, a means of strengthening intellectual capital, and a paradigm of cultural sustainability. The paper emphasizes lulament as a sonic document of existence and reflects on its potential applications within contemporary cultural policy and education.
Keywords: lulament, cultural heritage, voice, intimacy, affect, intangible culture, artistic research, cultural management, lullaby, lament